Group-Buying Deal Popularity. (March 2014) - Luo, Xueming; Andrews, Michelle; Song, Yiping; Aspara, Jaakko
Group-buying (GB) deals entail a two-phase decision process. First, consumers decide whether to buy a deal. Second, they decide when to redeem the deal, conditional on purchase. Guided by theories of social influence and observational learning, the authors develop a framework predicting that (1) deal popularity increases consumers' purchase likelihood and decreases redemption time, conditional on purchase, and (2) the social influence–related factors of referral intensity and group consumption amplify these effects. The authors test this framework and support it using a unique data set of 30, 272 customers of a GB website with several million data points. Substantially, these findings reveal a two-phase perspective of GB, longevity effects of deal popularity, and the amplifying role of customer referrals (influencing others) in the effects of deal popularity (others' influence). In light of the criticism of GB industry practice, this study builds the case for GB websites and merchants to heed deal popularity information and the social influence–related contingencies.